STOCK MOVEMENT ANALYSIS OF ONLINE MARKETPLACE IN INDONESIA USING LONG-SHORT TERM MEMORY MODEL WITH HYPERPARAMETER TUNING - Miranda, Shereva
Physics is the science that studies the structure of matter and the interactions between the fundamental elements of the observable universe. Physics can offer new perspectives in addressing economic issues. The stock market, categorized as a complex system with elements interacting in an irregular manner, can benefit from a physics-based approach in its analysis. E-commerce businesses or marketplaces that have achieved billion-dollar valuations have become major components of the stock market and an increasingly popular investment option. Due to the complexity of market movements, various methods are used for predicting market trends, including technical analysis, machine learning models,